2009
DOI: 10.1677/erc-09-0070
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer stromal cells and LNCaP cells coordinately activate the androgen receptor through synthesis of testosterone and dihydrotestosterone from dehydroepiandrosterone

Abstract: One of the mechanisms through which advanced prostate cancer (PCa) usually relapses after androgen deprivation therapy (ADT) is the adaptation to residual androgens in PCa tissue. It has been observed that androgen biosynthesis in PCa tissue plays an important role in this adaptation. In the present study, we investigated how stromal cells affect adrenal androgen dehydroepiandrosterone (DHEA) metabolism in androgen-sensitive PCa LNCaP cells. DHEA alone had little effect on prostate-specific antigen (PSA) promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
63
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 48 publications
2
63
0
Order By: Relevance
“…However, the development and incidence of BPH are associated with dysregulation of androgens, and with increased proliferation and decreased apoptosis of cells in the prostate gland. [4][5][6][7][8][9] Testosterone and dihydrotestosterone (DHT) have key roles in the development and growth of the entire male genital tract, and they stimulate differentiation of the prostate gland. 10,11) The adrenal glands and testes synthesize testosterone, and prostatic 5α-reductase type 2 converts it to DHT.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the development and incidence of BPH are associated with dysregulation of androgens, and with increased proliferation and decreased apoptosis of cells in the prostate gland. [4][5][6][7][8][9] Testosterone and dihydrotestosterone (DHT) have key roles in the development and growth of the entire male genital tract, and they stimulate differentiation of the prostate gland. 10,11) The adrenal glands and testes synthesize testosterone, and prostatic 5α-reductase type 2 converts it to DHT.…”
mentioning
confidence: 99%
“…12) DHT then binds to the androgen receptor (AR), which is transported to the nucleus, where it regulates genes important for prostate growth and differentiation. 4) BPH development and progression are associated with activation of the AKT pathway, a major growth factor-mediated signal transduction pathways. 6) Over-stimulation of the AKT pathway increases the activity of B-cell lymphoma 2 (Bcl-2) and cyclin D1, leading to increased proliferation and decreased apoptosis of cells, and transformation to the malignant state.…”
mentioning
confidence: 99%
“…Mizokami et al have clarified how prostate and bone stromal cells are able to convert DHEA into testosterone thereby increasing the local concentration of useful androgens within primary tumors and metastases respectively. 6 Moreover, this study provides evidence that dutasteride may inhibit the conversion of DHEA into testosterone.…”
mentioning
confidence: 63%
“…such as dehydroepiandrosterone (DHEA) as well as estradiol and androstenediol. 6 ADT may actually be responsible for the aforementioned changes because only those cells that develop the ability to survive in low androgen concentration survive and proliferate. 2 Though it is known that in most cases ADT only partially reduces the original tumor androgen concentration, despite drastic decreases in serum androgen concentration;…”
mentioning
confidence: 99%
“…The enzymatic conversion of DHEA to DHT has been shown to be essential for the activation of AR in LNCaP prostate cancer cells (Evaul et al 2010), while in vitro studies have shown that prostate cancer stromal cells and human LNCaP prostatic cancer cells coordinate activation of AR via synthesis of testosterone and DHT from DHEA (Mizokami et al 2009). In addition, increased expression of genes that code for the enzymes that convert DHEA into testosterone has been observed in CRPC (Stanbrough et al 2006), while cancerous prostatic tissue can synthesize more DHT than does benign prostatic tissue (Nishiyama et al 2007).…”
Section: Mechanisms Of Resistance To Castrationmentioning
confidence: 99%